2008
DOI: 10.1163/157006608x262700
|View full text |Cite
|
Sign up to set email alerts
|

'Healing of Bodies, Salvation of Souls': Missionary Medicine in Colonial Tanganyika, 1870s-1939

Abstract: Th is paper re-examines missionary medicine in Tanganyika, considering its relationship with the colonial state, the impulses that led it to evolve in the way that it did, and the nature of the medical services it offered. Th e paper suggests that, contrary to traditional depictions, missionary medicine was not entirely curative in focus, small in scale, nor inappropriate to the health needs of the communities in which it was based. Rather, missionary medicine should be considered as a vital aspect of early co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 6 publications
0
31
0
Order By: Relevance
“…Furthermore, the Tanzanian non-profit sector has delivered a large number of micro-finance initiatives in recent years (Mori & Fulgence, 2009). NPOs have been offering financial services that they adapted from the Grameen model and 6 There have been a number of criticisms of these 'Ujamaa' village policies as some authors have suggested that they were closer to soviet models of collectivisation and that the collectivisation of the land and of agricultural production has been impossible to achieve in Tanzania; see Hyden (2008) and Jennings (2002Jennings ( , 2003Jennings ( , 2008 for more details. 7 Structural Adjustment Programmes comprised a set of conditions imposed on governments in developing countries to balance their economies, such as privatisation of social programmes, reductions in welfare spending and free-market reforms (Giddens, 2009).…”
Section: Historical Evolution Of Socially Oriented Enterprise Activitmentioning
confidence: 99%
“…Furthermore, the Tanzanian non-profit sector has delivered a large number of micro-finance initiatives in recent years (Mori & Fulgence, 2009). NPOs have been offering financial services that they adapted from the Grameen model and 6 There have been a number of criticisms of these 'Ujamaa' village policies as some authors have suggested that they were closer to soviet models of collectivisation and that the collectivisation of the land and of agricultural production has been impossible to achieve in Tanzania; see Hyden (2008) and Jennings (2002Jennings ( , 2003Jennings ( , 2008 for more details. 7 Structural Adjustment Programmes comprised a set of conditions imposed on governments in developing countries to balance their economies, such as privatisation of social programmes, reductions in welfare spending and free-market reforms (Giddens, 2009).…”
Section: Historical Evolution Of Socially Oriented Enterprise Activitmentioning
confidence: 99%
“…They had been inspired from a variety of sources to use their skills to 'heal bodies and souls' (Jennings 2008). With their medical qualifications (and religious convictions), they went to work in remote locations, running hospitals, and dispensaries with limited funds and staff.…”
Section: Becoming a Missionarymentioning
confidence: 99%
“…16 In 1895, a former worker of the English Red Cross, Kate Marsden, founded the St. Francis Leper Guild in 1895, which became a Catholic charity supporting the work of leprosy settlements predominantly in the British Empire. 17 The pre-existing Mission to Lepers expanded its work from India to other parts of the British Empire in 1891, founding leprosy settlements and subsidising leprosy treatment by Protestant missions. 18 The British interest in philanthropy and welfare continued into the twentieth century, and in the wake of World War I, British leprosy charities experienced another surge.…”
Section: Leprosy's Emergence As a Humanitarian Cause In The British Ementioning
confidence: 99%